Kajian terkait ketangkasan belajar tenaga kerja pada perusahaan manufacturing di era digital - Wardatur Roikhah; Evita Purnaningrum; Heny Afifatul Mu’asyaroh (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
Abstract. Digital transformation plays an important role in changing the shape of a person's behavior along with increasingly advanced technology. Current technological developments require businesses to have an agile workforce and talented employees. Speed in learning is forced to be positively correlated with technological developments. The purpose of this research is to determine the competency readiness of the workforce through the learning agility of each individual. The factors investigated include learning culture, work involvement in Industry 4.0 by adjusting the contents of the questionnaire related to the Digital era. A quantitative method approach based on SEM-PLS with R software and plspm Package is used to determine the relationship between learning culture (X1) and work engagement (X2) with learning agility (Y) as a latent variable. The results of this study indicate that learning agility to achieve workforce readiness in the digital era can be influenced by learning culture and work enggagement. Keywords: Learning Agility; Learning Culture; Work Enggagement; Digital Era Abstrak. Transformasi digital memainkan peran penting pada perubahan bentuk tingkah laku seseorang bersanding dengan teknologi semakin maju. Perkembangan teknologi saat ini menuntut bisnis untuk memiliki tenaga kerja yang gesit dan karyawan yang berbakat. Kecepatan dalam belajar dipaksa berkorelasi positif dengan perkembangan teknologi. Tujuan penelitian ini adalah untuk mengetahui kesiapan kompetensi tenaga kerja melalui ketangkasan belajar dari setiap individunya. Faktor-faktor yang diselidiki meliputi budaya belajar, keterlibatan kerja di Industri 4.0 dengan menyesuaikan isi kuisioner terkait era Digital. Pendekatan metode kuantitatif berbasis SEM-PLS dengan software R dan plspm Package digunakan untuk mengetahui hubungan budaya belajar (X1) dan keterikatan kerja (X2) dengan ketangkasan belajar (Y) sebagai variabel laten. Hasil penelitian ini menunjukkan bahwa ketangkasan belajar untuk menju kesiapan tenaga kerja di era digital dapat dipengaruhi learning culture dan work enggagement. Katakunci: Ketangkasan Belajar;Budaya Belajar;Keterikatan Kerja; Era Digital